Dovyalis hebecarpa propagation by the use of cuttings - Almeida, Eduardo José de [UNESP]; De Jesus, Natanael; Scaloppi Jr., Erivaldo José; Moreira, Ricardo Franco Cunha [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (Taylor & Francis, 2007)
The vegetative propagation of Dovyalis hebecarpawas studied using herbaceous cuttings of a hybrid introduced in Brazil by the College of Agriculture, Campus of Jaboticabal-UNESP. The treatments consisted of (1) evaluating the effect of five 3-Indolebutyric acid (IBA) doses (0 (control), 1,000, 3,000, 5,000 and 7,000 mg.L -1); (2) the influence of two kinds of herbaceous cuttings (apical and sub-apical) and (3) the collection position on the plant (upper and lower part of the canopy) at two different times of the year (autumn and spring). The experimental design was completely randomized with four replicates of 10 cuttings each; the analysis was on a 5 × 2 × 2 factorial layout. The growth regulator (IBA) did not influence the rooting of cuttings in either sampling season. The best season for the rooting was spring. Apical cuttings were desirable for rooting in both seasons. In autumn cuttings taken from the lower portion of the plant showed significantly higher rooting values than the ones from the upper portion; and in spring cuttings taken from the upper portion had higher rooting percentages. © 2007 by The Haworth Press. All rights reserved.
Keywords: Ceylon gooseberry; Exotic fruit; Ketembilla; Kitembila; Rooting; Vegetative propagation; autumn; experimental design; fruit; growth regulator; hybrid; invasive species; rooting; shrub; spring (season); vegetative propagation; Dovyalis; Dovyalis hebecarpa